2023
DOI: 10.2147/ndt.s435138
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Factors Associated with Subclinical Hypothyroidism in Major Depressive Disorder Patients with Dyslipidemia

Luyu Zhan,
Huimin Yin,
Yujun Gao
et al.

Abstract: Background: Major depressive disorder (MDD) is a common psychiatric disorder with a high prevalence of comorbidity with subclinical hypothyroidism. The aim of this study was to investigate the prevalence and factors influencing the comorbidity of subclinical hypothyroidism in patients with dyslipidemic MDD who were hospitalized for the first time in a Chinese population. Methods:The study incorporated 708 first-time hospitalized MDD patients, all with dyslipidemia. Data collection encompassed socio-demographic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 50 publications
(57 reference statements)
3
1
0
Order By: Relevance
“…Hence, being married is linked to a higher likelihood of having SCH, possibly due to increased stress associated with married life. These observations were consistent with the observations of Zhan L, et al in their study [ 20 ]. Binary logistic regression for the phase of the menstrual cycle (secretory and proliferative) showed an odds ratio of 1.53, indicating that women in the secretory phase perceived a greater amount of stress, which is similar to the findings of Jain P, et al in their study.…”
Section: Discussionsupporting
confidence: 94%
“…Hence, being married is linked to a higher likelihood of having SCH, possibly due to increased stress associated with married life. These observations were consistent with the observations of Zhan L, et al in their study [ 20 ]. Binary logistic regression for the phase of the menstrual cycle (secretory and proliferative) showed an odds ratio of 1.53, indicating that women in the secretory phase perceived a greater amount of stress, which is similar to the findings of Jain P, et al in their study.…”
Section: Discussionsupporting
confidence: 94%
“…Consistent with our findings, previous studies have documented the substantial association of subclinical hypothyroidism with worse clinical symptoms in MDD. 24 26 Our results, if confirmed in further large-scale studies, highlight the importance of autoimmune thyroiditis severity levels in both clinical practice and future research.…”
Section: Discussionsupporting
confidence: 67%
“…Consistent with our findings, previous studies have documented the substantial association of subclinical hypothyroidism with worse clinical symptoms in MDD. [24][25][26] Our results, if confirmed in further large-scale studies, highlight the importance of autoimmune thyroiditis severity levels in both clinical practice and future research. Consistent with prior studies in patients with MDD, 10,12 we found significantly higher autoimmune thyroid antibodies and TSH levels in patients with a history of suicide attempt.…”
Section: Discussionsupporting
confidence: 62%
“…As well, LDL-induced endothelial dysfunction is implicated in the pathogenesis of AS [ 123 ]. Furthermore, subclinical PHT can trigger the development of endothelial dysfunction through the induction of dyslipidemia [ 124 ]. It has been illustrated that increasing TSH level in subclinical PHT is positively correlated with serum triglyceride, cholesterol, and LDL, and negatively correlated with serum HDL level [ 125 ].…”
Section: Tsh In the Pathogenesis Of Asmentioning
confidence: 99%